Когнитивное моделирование факторов, влияющих на криминализацию общества, в целях принятия управленческих решений в сфере борьбы с преступностью - Суходолов, А. П. (ТюмГУ, 2020)
Мета роботи полягала у виявленні базисних факторів, що впливають на криміналізацію суспільства, з використанням когнітивного підходу, орієнтованого на те, щоб активізувати інтелектуальні процеси кримінологи-аналітики і допомогти йому зафіксувати своє уявлення про проблемну ситуацію у вигляді формальної моделі, а потім розробити і обґрунтувати управління цією ситуацією. В основу побудови формальної моделі лягли результати опитування осіб, які не є фахівцями у галузі юриспруденції, й експертів у цій сфері. У результаті було сформовано дві когнітивні структури криміногенних і антикріміногенних факторів. З метою дослідження системних характеристик стійкості і чутливості даних структур проведені відповідні імітаційні експерименти. The goal of this work was to identify basic factors that influence the criminalization of the society using the cognitive approach oriented at intensifying the intellectual activity of a criminologist-analyst and helping them express their understanding of a problem situation through a formal model, and then work out and support a managerial decision for this situation. The formal model was developed on the basis of a survey that included both people who are not specialists in the sphere of law, and experts in this sphere. As a result, the authors designed two cognitive structures for criminogenic and anti-criminogenic factors. Simulation experiments were carried out to research the systemic characteristics of sustainability and sensitivity of these structures. Simplicial analysis was conducted to identify implicit connections between factors, its results were then used to form new cognitive structures and conduct another set of simulation experiments. It was stated that, among the managing factors named by experts, the key ones are the level of alcohol addiction of the population and the moral principles established in the society, while the key factors among those named by non-experts are «latent crimes» and «moral principles». Thus, the authors established that the opinions of experts and laymen differ, but they coincide in the factor «moral principles». Non-experts stressed the factor of the variety of crimes, while experts stressed the factor influencing the lives of people. When making managerial decisions, law enforcement employees should not only use the opinion of specialists, but also take into consideration the opinion of ordinary citizens. The conducted research is thus aimed at comparing the identified factors and at finding links between them with the purpose of justifying and supporting effective decisions in the sphere of crime counteraction.
Когнітивне моделювання факторів, що впливають на криміналізацію суспільства, з метою прийняття управлінських рішень у сфері боротьби зі злочинністю
Cognitive modeling of factors that influence the criminalization of society in making managerial decisions in the sphere of crime counteraction
Keywords: криміналізація; когнітивна модель; симпліціальний аналіз; імітаційний експеримент; Criminalization; cognitive model; simplicial analysis; simulation experiment